Efektivitas Penggunaan Fitur Facebook Advertising dalam Meningkatan Penjualan Produk Jilbab - Kartiah, Desty Dwi Saputri; Purnamie Titisari; Akhmad Munir (UPT Penerbitan Universitas Jember, 2025)
This study aims to determine the effectiveness of using Facebook advertising features in increasing sales of jilbab products at Alwani Nusantara Production House, Nangkaan District, Bondowoso Regency. The method used is qualitative analysis with a case study approach. The research data comes from primary data obtained through interviews, observations, and documentation, while secondary data is obtained from documents, journals, and websites relevant to the research. The results show that the use of Facebook advertising still has the potential to increase sales, despite a decline in sales data from 2022 to 2024. Factors such as ad duration and content quality significantly influence consumer interest and purchasing decisions. This research recommends that Alwani Nusantara explore other promotional media to optimize their marketing strategy.